Boron–Ligand Cooperation: The Concept and Applications. Issue 18 (28th January 2021) - Hasenbeck, Max; Gellrich, Urs
Abstract: The term boron–ligand cooperation was introduced to describe a specific mode of action by which certain metal‐free systems activate chemical bonds. The main characteristic of this mode of action is that one covalently bound substituent at the boron is actively involved in the bond activation process and changes to a datively bound ligand in the course of the bond activation. Within this review, how the term boron–ligand cooperation evolved is reflected on and examples of bond activation by boron–ligand cooperation are discussed. It is furthermore shown that systems that operate via boron–ligand cooperation can complement the reactivity of classic intramolecular frustrated Lewis pairs and applications of this new concept for metal‐free catalysis are summarized. Abstract : B for cooperation : The term boron–ligand cooperation (BLC) describes a specific mode of action by which distinctive intramolecular borane‐based frustrated Lewis Pairs (FLPs) activate chemical bonds. The central aspect of this concept is that the substituent at the borane that is involved in the bond activation becomes a datively bound ligand upon bond activation. The reactivity of systems that operate via BLC can complement those of classic intramolecular FLPs.